Larvae of two East-Asian species of Nemoura (Plecoptera: Nemouridae) - Teslenko, Valentina A. (Zootaxa, 2016)
Associated larvae of the two East-Asian Nemoura species, N. papilla Okamoto and N. ussuriensis Zhiltzova are described and illustrated in detail for the first time. The main diagnostic features of late instar larvae of both species are color and pigment patterns, the chaetotaxy of the pronotum, legs, abdomen, and cercal segments.